Landfill leachate treatment by sorption in magnetic particles: preliminary study - Paulo A. Augusto (2019)
Leachates are still an open issue in environmental protection. Many of the applied methods for their treatment present low efficiency and thus need to be used collectively. In practice reverse osmosis is mostly used, as it is the most effective option, regardless of its cost. Magnetic methods to treat effluents have been used for water and wastewater treatment by the use of magnetic particles together with magnetic separation for the removal of contaminants. However, large-scale applications are few or even non-existent when we deal with complex contaminated media such as landfill leachates, for which not even research studies at laboratorial scale with real samples have been done yet. In this work, we apply for the first time magnetic sorption for the treatment of leachates, and close the full cycle by studying the regeneration and re-use of the magnetic particles; we also study the influence of the concentration of magnetic particles, the use of several pre-treatment methodologies and the type of particle used in the process, in real landfill samples from the waste treatment plant of Salamanca (Spain), for the removal of COD, NO3-, NO2-, NH4+, Total-N, PO43-, SO42- and Cl-. Regeneration of the magnetic particles alter being used in the sorption stage is also studied, as well as their efficiency regarding their re-use. It is also determined the optimum number of batches for complete desorption and for regeneration of the particles, the effect of successive regeneration and re-use cycles, the use of two different regeneration methods, the efficiency of the desorption, the effect of the quantity of solvent and the influence of the time of sorption. Due to its innovative character and the complexity of the media, this work represents a first preliminary approach and, although some promising results have been obtained, further studies are required to completely understand and evaluate the proposed treatment process.